Lao Economic Monitor, April 2017 : Challenges in Promoting More Inclusive Growth and Shared Prosperity - World Bank Group (World Bank, Washington, DC, 2017)
The Lao economy is estimated to have grown at around 7 percent in 2016, a slight moderation from 7.4 percent in the previous year. Inflation pressures remain low, though prices increased faster in the second half of the year as oil prices recovered. The fiscal deficit widened significantly in FY15/16 due to a revenue shortfall. Monetary policy was directed towards stimulating credit growth, with some success. The current account deficit improved in 2016. While the country has achieved strong economic development over the past decade, higher investment on human development, particularly on health services, has become one priority.